2014
DOI: 10.1021/cs501010x
|View full text |Cite
|
Sign up to set email alerts
|

Thiolate-Mediated Selectivity Control in Aerobic Alcohol Oxidation by Porous Carbon-Supported Au25 Clusters

Abstract: Supported Au25 clusters were prepared through the calcination of Au25(SC12H25)18 on hierarchically porous carbon nanosheets under vacuum at temperatures in the range of 400–500 °C for 2–4 h. TEM and EXAFS analyses revealed that the thiolate coverage on Au25 gradually decreased with increasing calcination temperature and period and became negligibly small when the calcination temperature exceeded 500 °C. The catalysis of these Au25 clusters was studied for the aerobic oxidation of benzyl alcohol. Interestingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
195
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(204 citation statements)
references
References 33 publications
7
195
2
Order By: Relevance
“…Such a speculation is reasonable, as Au 25 (PPh 3 ) 10 (PA) 5 X 2 was synthesized via a ligand exchange process in which some of the phosphine groups were replaced with phenylacetylide in the presence of amine (e.g., pyridine) [28]. The ligand removal phenomenon has already been reported [48][49][50][51][52][53][54]. For example, one phosphine ligand (e.g., PPh 3 and PPh 2 Py (diphenyl-2-pyridylphosphine)) of Au 11 (PPh 3 ) 7 Cl 3 and Au 11 (PPh 2 Py) 7 Cl 3 can leave the clusters in the presence of amine to provide an active site for the selective hydrogenation [55].…”
Section: Tentative a 3 -Coupling Mechanism Catalyzed By Au 25 Clustersmentioning
confidence: 87%
“…Such a speculation is reasonable, as Au 25 (PPh 3 ) 10 (PA) 5 X 2 was synthesized via a ligand exchange process in which some of the phosphine groups were replaced with phenylacetylide in the presence of amine (e.g., pyridine) [28]. The ligand removal phenomenon has already been reported [48][49][50][51][52][53][54]. For example, one phosphine ligand (e.g., PPh 3 and PPh 2 Py (diphenyl-2-pyridylphosphine)) of Au 11 (PPh 3 ) 7 Cl 3 and Au 11 (PPh 2 Py) 7 Cl 3 can leave the clusters in the presence of amine to provide an active site for the selective hydrogenation [55].…”
Section: Tentative a 3 -Coupling Mechanism Catalyzed By Au 25 Clustersmentioning
confidence: 87%
“…The reports on ligand-modulated selective oxidation using Au NPs are few. Yoskamtorn et al [24] reported that the surface ligands of supported Au 25 nanoclusters had a profound influence on the product selectivity of aerobic benzyl alcohol oxidation reaction (Figure 3). By reducing surface ligands through high-temperature calcination at 400-500 • C, as-resulted Au nanocatalysts exhibited a continuous decrease in selectivity to benzaldehyde from 100% to 15%, along with the increase of TOF.…”
Section: Steric Effect Of Surface Ligandsmentioning
confidence: 99%
“…A high selectivity to the hydrogenation of aldehyde groups (close to 100%) was attributed to the formation of -S(R)-Au-S(R)-Au-S(R) staple-like motifs, which resulted in the strong interaction of 4-nitrobenzaldehyde with C=O bonds. Reprinted with permission from [24]. Copyright American Chemical Society, 2014.…”
Section: Steric Effect Of Surface Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few years, significant advances have been made in the synthesis and property studies of these doping nanoclusters [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Among homogold nanoclusters, Au 25 (SR) 18 nanocluster has been well studied due to its stable structure among three different charges (−1/0/+1) [22][23][24][25][26], which led to the exploration of a wide range of catalytic pathways facilitated by Au 25 for organic reactions, such as oxidation [27][28][29], hydrogenation [30][31][32], electronic transfer reactions [26,33], and electrocatalysis [34,35]. Recent research implies that doping foreign atoms into this 25 noble metal system can largely affect the stability and the catalytic activity compared to the homogold counterpart [7][8][9][10][17][18][19].…”
Section: Introductionmentioning
confidence: 99%